Bridging silos through governance innovations: the role of the EU cities mission - Buylova, Alexandra; Nasiritousi, Naghmeh; Bergman, Jennifer; Sanderink, Lisa; Wickenberg, Björn; Casiano Flores, Cesar; McCormick, Kes (Frontiers in Sustainable Cities, 2025)
Cities and local governments are increasingly under pressure to accelerate transformative change in energy and climate transitions. To help cities in their climate actions, the European Commission (EC) has established the EU Cities Mission, which aims for climate neutrality by 2030 for participating cities. The literature argues that one of the main obstacles to accelerating decarbonization lies in organizational divisions and other forms of structural silos. One of the possible ways to address these challenges and accelerate transformation is through governance innovations. The EU Cities Mission is a governance innovation that aims to incentivize and support climate and energy transitions in cities. In this paper, we critically assess the EU Cities Mission’s framework and implementation plan in terms of its potential and possible gaps in addressing different types of silos. To do so, we develop an analytical framework based on academic literature that outlines types of silos and strategies for addressing them. Our results show that key EU Cities Mission documents include several strategies to bridge silos, but that some silos are less frequently addressed. This is particularly the case for silos that rely on political leadership. The paper concludes by drawing out the implications of our findings for the scholarly literature and practice.